2017
DOI: 10.15761/ohc.1000110
|View full text |Cite
|
Sign up to set email alerts
|

A series of 13 new cases of langerhans cell histiocytosis of the oral cavity: a master of disguise

Abstract: Langerhans cell histiocytosis(LCH) is a disease characterized by clonal proliferation and excessive accumulation of disseminated forms of dendritic Langerhans cells. The aims of thestudy were to describe clinico-pathological presentations of thirteen new cases of LCH of the oral cavity and to present its differential diagnoses. The majority of 61.53% (8/13) of cases occurred in infants and adolescents with female predominance (61.53%). Out of all the lesions,61.53 % occurred intraosseously;with majority 53.82%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In about 5%–75% of patients, oral manifestations are the first signs and symptoms and sometimes the only symptom of LCH, thus, prompting the patient to seek treatment from a dentist 8 . Eden P et al, reported in a case series ( n = 13) that seven of the cases showed intra‐osseous lesion in the posterior region of the jaw and oral mucosal involvement (tongue, buccal mucosa and gingiva) 9 . Sore throat, halitosis, gingivitis, gingival hypertrophy, unpleasant taste, tooth mobility with alveolar expansion, jaw pain, facial swelling, mental nerve anesthesia, and inability of extracted tooth sockets to heal are some of the oral symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In about 5%–75% of patients, oral manifestations are the first signs and symptoms and sometimes the only symptom of LCH, thus, prompting the patient to seek treatment from a dentist 8 . Eden P et al, reported in a case series ( n = 13) that seven of the cases showed intra‐osseous lesion in the posterior region of the jaw and oral mucosal involvement (tongue, buccal mucosa and gingiva) 9 . Sore throat, halitosis, gingivitis, gingival hypertrophy, unpleasant taste, tooth mobility with alveolar expansion, jaw pain, facial swelling, mental nerve anesthesia, and inability of extracted tooth sockets to heal are some of the oral symptoms.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Eden P et al, reported in a case series ( n = 13) that seven of the cases showed intra‐osseous lesion in the posterior region of the jaw and oral mucosal involvement (tongue, buccal mucosa and gingiva). 9 Sore throat, halitosis, gingivitis, gingival hypertrophy, unpleasant taste, tooth mobility with alveolar expansion, jaw pain, facial swelling, mental nerve anesthesia, and inability of extracted tooth sockets to heal are some of the oral symptoms. The loss of supporting alveolar bone may be mistaken for advanced periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The oral manifestations frequently intraosseous lesions, affection of posterior area of mandible, anterior mandible, soft tissues of buccal mucosa, gingiva and tongue (9,10). Eden P., et al, reported in a case series (n=13), 7 of the cases showed intra osseous lesion in the posterior region of the jaw and oral mucosal involvement (tongue, buccal mucosa and gingiva) (11).…”
Section: Introductionmentioning
confidence: 94%